2023
DOI: 10.3389/fmicb.2023.1121763
|View full text |Cite
|
Sign up to set email alerts
|

Infection and innate immune mechanism of goose astrovirus

Abstract: Goose astrovirus (GAstV, genus Avian Astrovirus, family Astrovirus) was first discovered in 2005, but was not considered as a pathogen of gosling gout until 2016. Since then, goose astrovirus has erupted in Chinese goslings, causing at most 50% of gosling deaths. By December 2022, the disease had become epidemic and prevailed in goose farms in Jiangsu, Shandong, Anhui, Henan, Guangdong, Liaoning, Sichuan and other places in China. The disease mainly affects goslings within 3 weeks old. The typical symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…It is expressed in various types of tissues, including the liver, kidney, and lung. Studies have demonstrated that MX1 influence the occurrence of apoptosis or programmed cell death, which is essential for the removal of damaged or infected cells ( Ciancanelli et al, 2016 ; Xu et al, 2023 ). Furthermore, MX1 maintains immune response processes by regulating T-cell proliferation and differentiation ( Sato et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in various types of tissues, including the liver, kidney, and lung. Studies have demonstrated that MX1 influence the occurrence of apoptosis or programmed cell death, which is essential for the removal of damaged or infected cells ( Ciancanelli et al, 2016 ; Xu et al, 2023 ). Furthermore, MX1 maintains immune response processes by regulating T-cell proliferation and differentiation ( Sato et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Microbiology 09 frontiersin.org contributes to the gradual formation of increased ammonia levels within the body (Xi et al, 2022). If the rate of urate production surpasses the excretion capacity of the urinary organs, it can result in uric acidemia (Xu et al, 2023). Some studies have demonstrated that a highly protein-rich diet for goslings can lead to crystal formation and gout (An et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This has significantly slowed the vaccine development progress, leaving the industry vulnerable to the virus' impact. 2 Furthermore, the shortage of commercially available antibodies specific to GAstV, and antibodies for the goose species, presents another major obstacle in the research path. These antibodies are crucial for studying the virus' structure, replication mechanism and immune response in the host.…”
Section: How To Submit a Letter Or Noticementioning
confidence: 99%
“…The current cell lines used for GAstV research, such as the primary goose embryonic kidney cells (GEK) and goose embryonic hepatocyte (GEH) cells, have limitations in their high production costs and limited passage times. This has significantly slowed the vaccine development progress, leaving the industry vulnerable to the virus' impact 2 …”
mentioning
confidence: 99%